GADD45γ regulates the thermogenic capacity of brown adipose tissue - Gantner, Marin L. (National Academy of Sciences, 2014)
The coactivator peroxisome proliferator-activated receptor-gamma coactivator 1 α (PGC-1α) is widely considered a central transcriptional regulator of adaptive thermogenesis in brown adipose tissue (BAT). However, mice lacking PGC-1α specifically in adipose tissue have only mild thermogenic defects, suggesting the presence of additional regulators. Using the activity of estrogen-related receptors (ERRs), downstream effectors of PGC-1α, as read-out in a high-throughput genome-wide cDNA screen, we identify here growth arrest and DNA-damage-inducible protein 45 γ (GADD45γ) as a cold-induced activator of uncoupling protein 1 (UCP1) and oxidative capacity in BAT. Mice lacking Gadd45γ have defects in Ucp1 induction and the thermogenic response to cold. GADD45γ works by activating MAPK p38, which is a potent activator of ERRβ and ERRγ transcriptional function. GADD45γ activates ERRγ independently of PGC-1 coactivators, yet synergizes with PGC-1α to induce the thermogenic program. Our findings elucidate a previously unidentified GADD45γ/p38/ERRγ pathway that regulates BAT thermogenesis and may enable new approaches for the stimulation of energy expenditure. Our study also implicates GADD45 proteins as general metabolic regulators.